A summary of the ComParE COVID-19 challenges - Harry Coppock; Alican Akman; Christian Bergler; Maurice Gerczuk; Chloë Brown; Jagmohan Chauhan; Andreas Grammenos; Apinan Hasthanasombat; Dimitris Spathis; Tong Xia; Pietro Cicuta; Jing Han; et al. (Frontiers in Digital Health, 2023)
The COVID-19 pandemic has caused massive humanitarian and economic damage. Teams of scientists from a broad range of disciplines have searched for methods to help governments and communities combat the disease. One avenue from the machine learning field which has been explored is the prospect of a digital mass test which can detect COVID-19 from infected individuals’ respiratory sounds. We present a summary of the results from the INTERSPEECH 2021 Computational Paralinguistics Challenges: COVID-19 Cough, (CCS) and COVID-19 Speech, (CSS).